International Rotations in Globally Networked Public Accounting Firms: Brokering Quality Control - Westermann, Kimberly D.; Downey, Denise Hanes (The Accounting Review, 2025)
ABSTRACT This study aims to understand international rotations (“secondments”) as a brokerage mechanism within globally networked public accounting firms (GNFs). Through interviews with 29 secondees on tour to or from the U.S. (individuals on rotation from one member firm to another member firm in a specified role for a fixed period) and 11 firm leaders, we find that secondments are viewed as a critical brokerage function in performing global client service and global risk management. Specifically, secondees bridge gaps in the GNF structure by brokering network ties, technical knowledge, sociocultural knowledge, and language. Secondees embody different brokerage roles and can fulfill more than one brokerage role at a time, depending on the purpose of the secondment and the stage of deployment. Collectively, secondments are important mechanisms by which structural holes are reduced between participating member firms and proximal member firms, ultimately benefiting the global firm and the global clients they serve.